Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Pada PT. X - Zahra, Ardiyani; Ramayani Yusuf (Universitas Haji Sumatera Utara, 2024)
This research examines the relationship between Organizational Culture and Employee Performance at PT X. By applying the Simple Linear Regression Analysis method, this study attempts to measure the extent to which Organizational Culture affects Employee Performance. Data was collected through a survey given to employees of PT X. The results showed that Organizational Culture has a significant positive influence on Employee Performance. In conclusion, companies with a strong culture tend to have more productive and high-performing employees. Some aspects of Organizational Culture, such as open communication, support for innovation, and a fair reward system, are proven to make a meaningful positive contribution to employee performance.